DEIXIS : USES AND REASONS OF THEIR USING IN OPERA VAN JAVA - Meylitasri, Deka (2012)
The present research entitled Deixis: Uses and Reasons of Their Using In Opera Van Java. It aims to investigate the use of deixes in Opera Van Java by identifying the types of deixis and reasons of using the deixes. The researcher used theory of Yule (1996) and Hymes (Saputra, 2010). The analysis was done by analyzing dialogues of puppets in Opera Van Java. There were four titles of show in Opera Van Java used as samples of the research. The dialogues of the shows were collected by using video recorder. The findings show that the puppets in Opera Van Java use the three types of deixis: person, temporal, and spatial deixis. The type of deixis mostly used by the puppets is person deixis in order to make the dialogues funny. The uses of deixis are influenced by several factors, e.g. purposes of humor, the characteristics of the addressee, and background of the speaker. The puppets realize that the purposes of humor are the main reasons to use the deixis. They sometimes used inappropriate deixis to make dialogue funny.